Ensino de probabilidade : uma proposta de sequência didática com uso dos jogos Bozó e Coup - Alves, Luis Paulo de Souza (2021)
Didactic sequence is an important tool for organizing educational practice, it guides and systematizes such practice. Because of this, it is necessary that this instrument adapts at students’ demands, and one of these demands is that knowledge be practical and part of their daily lives. In this regard, the use of games presents itself as an important tool to be able to make an approximation of mathematical concepts, in this case concepts of probability, daily life, and for being inserted in a playful way, sharpening student’s curiosity. The main objective of this research is to verify if the use of the Bozó and Coup games for the preparation and application of a didactic sequence on probability facilitates the understanding of the worked concepts. For this purpose, a thematic approach was formulated following the guidelines of the Common National Curriculum Base (BNCC) and, according to its requirements, a didactic sequence was structured and applied using the aforementioned games with students from a 9th grade class of elementary school at Leibniz School from Rondonópolis. After the application, a qualitative research was carried out using the technique called heremeneutic-dialectic circle of data collection, through an oral presentation of their evaluation of the didactic sequence and learning itself, answering individual questionnaires with the same regards, and through the analysis of the answers of the activities carried out by those involved. It was found that the use of games contributed in a positive way, which can be verified mainly by the greater involvement of students, by verifying the practice of writing activity with games still in hand, and by the untying of problem solving with ready-made formulas.